Exam Ref AZ-305 : designing Microsoft Azure infrastructure solutions - Agrawal, Ashish; Singh, Gurvinder; Bhavsar, Avinash; Sopariwala, Mohammad Sabir (Pearson Education, 2023)
Prepare for Microsoft Exam AZ-305 and help demonstrate your real-world expertise in designing cloud and hybrid solutions that run on Microsoft Azure, including identity, governance, monitoring, data storage, business continuity, and infrastructure. Designed for modern IT professionals, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Expert level. Exam AZ-305 focuses on knowledge needed to design logging, monitoring, authentication, and authorization solutions; design governance, identities, and application access; design relational and non-relational data storage solutions; design data integration; recommend data storage solutions; design backup and disaster recovery solutions; design for high availability; design compute and network solutions, application architecture, and migration.